Carbon Nanotubes for Clean Water (Carbon Nanostructures,, 2018)
This book presents carbon nanotubes as a potential material for the development of new waste water treatment technologies. Reviews on adsorption, catalysis, membrane, filtration and desinfection methods are provided. A special chapter presents the use of carbon nanotubes to sense and monitor water pollutants. The text underlies each technology and process as well as the current commercialization efforts. Research gaps are highlighted at the end with links to further reading material in the field.